Freedom through law - Lubogo, Isaac Christopher (Jescho Publishing House, 2021)
“If the legal system or a particular law is wrong or not good enough, and should be changed: if that is against the law, then the law is an ass – an idiot….” said of a law that one thinks is unnecessary or ridiculous. The phrase comes from Charles Dickens Novel, Oliver Twist. This opinion was expressed by Mr. Bumble, when he learned from Mr. Brownlow that, under Victorian law, he was responsible for actions carried out by his wife. His words and action vividly convey the extent of his indignation when he apprised of this legal fact, if that’s the eye of the law, the law is a bachelor: and the worst I wish the law is that his eye may be opened by experience. (Resonate with changing society) This is the very purpose of this book. The law should be seen to resonate with changing society not a dogma for if we fail to do so then to use Shakespeareʼs exact line by the famous plotter of treachery “ the first thing we do, letʼs kill all the lawyers” this was stated by Dick the Butcher, in Henry VI part II, Act IV, Scene II, LINE 73 Dick the Butcher was a follower of the rebel Jack Cade, who thought that if he disturbed law order, he could become king. Shakespeare meant it as a compliment to attorneys and judges who instill justice in society. It is among Shakespeareʼs most famous lines, as well as one of his most controversial. Shakespeare may be making a joke when character “Dick the Butcher” suggests one of the ways the band of pretenders to the throne can improve the country is to kill all the lawyers. Dick is a rough character, a killer as evil as his name implies like the other henchmen, and this is his rough solution to his perceived societal problem. The line has been interpreted in different ways: criticism of how lawyers maintain the privilege of the wealthy and powerful; implicit praise of how lawyers(law) emphasis added stand in the way of violent mobs; and criticism of bureaucracy and perversions of the rule of law under THE NAME OF DOGMA
Keywords: Jurisprudence; Freedom - Legal aspects; Law and freedom